A territorialidade da fé a Nossa Senhora da Abadia no município de Ituiutaba-MG - Gonçalves, Karina Corrêa do Carmo (2022)
Considering territoriality as a strategy of space control, it becomes possible to form the idea of religious territoriality characterized by the set of practices developed by institutions or religious groups in the sense of controlling a certain territory where the effect of the power of faith reflects an identity of faith and a sense of mutual ownership. The study of this religious identity makes it possible to identify points in the territory of sacred places that present themselves in centers of convergence and religious irradiation dedicated to Nossa Senhora da Abadia from Portugal. Such devotion arises along with the city of Ituiutaba-MG, accompanies its growth and begins to attract devotees from all parts of the city and neighboring municipalities, resulting in the prolongation of the festive time in praise of the saint and her ways of worship. expression, exploring the symbology attributed to this sacred place to analyze it as a center of convergence and irradiation of the Catholic faith. A qualitative research was developed, mostly exploratory and descriptive, based on bibliographic reviews, document analysis, survey through semi-structured interviews, also carrying out data collection together with the religious institutions of the municipality, in addition to using information obtained in work relevant to the study of the case under study. Throughout the text, it is possible to follow the emergence and development of Marian devotion in ItuiutabaMG and its characterization as a Catholic sacred place recognized by the local population, becoming a reference for the population of neighboring municipalities.